2010
DOI: 10.1038/cddis.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of the JNK/c-Jun/AP-1 signaling pathway in galectin-1-induced T-cell death

Abstract: Galectin-1 (gal-1), an endogenous β-galactoside-binding protein, triggers T-cell death through several mechanisms including the death receptor and the mitochondrial apoptotic pathway. In this study we first show that gal-1 initiates the activation of c-Jun N-terminal kinase (JNK), mitogen-activated protein kinase kinase 4 (MKK4), and MKK7 as upstream JNK activators in Jurkat T cells. Inhibition of JNK activation with sphingomyelinase inhibitors (20 μM desipramine, 20 μM imipramine), with the protein kinase C-δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 46 publications
1
40
1
2
Order By: Relevance
“…Finally, it has been previously shown that endothelial cells secrete Galectin-1 upon inflammatory conditions (34). Moreover, Galectin-1 can induce apoptosis of T lymphocytes and can regulate bcl-2 expression (35,36). Along the same line, CD146 expression is both up-regulated at the membrane and secreted after TNF␣ treatment (12), and its overexpression leads to activation of survival and anti-apoptotic pathways (37).…”
mentioning
confidence: 81%
“…Finally, it has been previously shown that endothelial cells secrete Galectin-1 upon inflammatory conditions (34). Moreover, Galectin-1 can induce apoptosis of T lymphocytes and can regulate bcl-2 expression (35,36). Along the same line, CD146 expression is both up-regulated at the membrane and secreted after TNF␣ treatment (12), and its overexpression leads to activation of survival and anti-apoptotic pathways (37).…”
mentioning
confidence: 81%
“…In sharp contrast with our findings about gal-9, several of these studies pointed out some kind of interdependence between T cell activation and apoptosis induction. For example, Brandt et al (59) reported apoptosis induction in Jurkat cells treated with galectin-1 requiring an intact TCR-CD3 complex. It is important to notice that in the study of Brandt et al (59), the concentrations of galectin-1 were in the range of 600 -1800 nM instead of about 30 nM gal-9 in our own work.…”
Section: Th1 Cytokines Il-2 and Ifn␥ In Jurkat Cells As Well As Inmentioning
confidence: 99%
“…41 Mechanistically, this lectin triggers endonuclease G nuclear translocation, 42 p56/Lck tyrosine phosphorylation 43 and activator protein-1 activation. 44,45 Moreover, galectin-1 stimulates the release of ceramide and promotes c-Jun N-terminal kinase (JNK) activation. As a result, Bcl-2 accumulation is condensed and Bcl-2 phosphorylation is elevated, generating heterodimerization with the proapoptotic protein Bax.…”
Section: Galectin Counter-receptors In the Initiation Of Cell Deathmentioning
confidence: 99%
“…These molecular events lead to caspase-3 and -9 activation resulting in T-cell death. 45 Expression of core-2 O-glycans (Galb1-3 [N-acetyl glucosamine] b1-6 GalNAc) on the surface of T cells allows clustering of CD45, which facilitates galectin-1-induced apoptosis. 46 The absence of this glycan and particularly the presence of a2-6-linked sialic acid on CD45 N-glycans counteract inhibition of CD45 tyrosine phosphatase activity, which is an essential step in galectin-1-induced cell death.…”
Section: Galectin Counter-receptors In the Initiation Of Cell Deathmentioning
confidence: 99%